Opening Up Classroom Doors: English Teachers’ Curriculum Fidelity and Adaptations - Fatma Mine ARSLAN-ÇELİK; Sevinç GELMEZ-BURAKGAZİ (Hayef: Journal of Education)
The fidelity of implementing curriculum is acting by adhering to the original content without making any modifications by the individuals responsible for implement ing it. Therefore, the implementation phase and the process should be focused on reaching a correct evaluation of outcomes. This research examines the teachers’ f idelity to implementing the curriculum and the factors involved in the teachers fidelity. Drawing on a multiple nested case study research design, this study analyzes a data set gathered from interview and classroom observation forms developed by researchers, students’ notebooks, class books, textbooks, curriculum, and more. The data were examined through content analysis utilizing the MAXQDA12 software. The findings explicate heterogeneity of the teachers’ fidelity of implementation that has roots in the facilities of the school, participant idiosyncrasies, the course materials, the characteristics of the program elements, and teacher particularities who is the program practitioner.